2016
DOI: 10.4049/jimmunol.1600541
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Adenovirus Type 4 (Species E) E3-19K/HLA-A2 Complex Reveals Species-Specific Features in MHC Class I Recognition

Abstract: Adenoviruses (Ads) subvert MHC class I antigen presentation and impair host anti-Ad cellular activities. Specifically, the Ad-encoded E3-19K immunomodulatory protein targets MHC class I molecules for retention within the endoplasmic reticulum (ER) of infected cells. Here, we report the x-ray crystal structure of the Ad type 4 (Ad4) E3-19K of species E bound to HLA-A2 at 2.64 Å resolution. Structural analysis shows that Ad4 E3-19K adopts a tertiary fold that is shared only with Ad2 E3-19K of species C. A compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…). This binding mode was also seen in the X‐ray structure of the HAdV‐E4 E3‐19K/HLA‐A2 complex . These structures provided critical information to understand that the conserved residues form a tightly packed hydrophobic core essential to maintain the unique tertiary fold of E3‐19K (Fig.…”
Section: E3‐19k and Other E3 Proteinsmentioning
confidence: 61%
“…). This binding mode was also seen in the X‐ray structure of the HAdV‐E4 E3‐19K/HLA‐A2 complex . These structures provided critical information to understand that the conserved residues form a tightly packed hydrophobic core essential to maintain the unique tertiary fold of E3‐19K (Fig.…”
Section: E3‐19k and Other E3 Proteinsmentioning
confidence: 61%
“…In Loop L3 there are no such determinants [ 3 ]. Lenong, 2016 [ 4 ] indicated that three structure of Ad type2 (Ad2) of species CE3-19K/HLA-A2 complex showed the adaptation of a novel tertiary fold, and uses a new binding surface on HLA-A2. The adenoviruses encoded E3-19K immunomodulatory protein targets MHC class I molecules for retention within the endoplasmic reticulum (ER).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 7(b), a strand is missing from the -sheet of the 3 subunit of HLA in PDB entry 5iro (Li et al, 2016), a protein complex of Adenovirus type 4 E3-19K with HLA class I histocompatibility antigen. By optimization of the structure model by PDB-REDO including loop building, the R/R free drops from 0.220/0.236 to 0.182/ 0.190.…”
Section: Examples Of Built Loopsmentioning
confidence: 99%